Creating a Choose-Your-Own-Adventure Library Orientation - Amber Sewell (Journal of New Librarianship, 2021)
When in-person instruction was taken off the table, a new virtual orientation to the library was needed. Striving to create a balance of informational and engaging content, this article describes the thought- and creation-process behind a choose-your-own-library-adventure game built with the online tool Twine, and includes feedback and revisions made based on the Fall 2020 semester.